Time trends and factors associated with breastfeeding in the state of Pernambuco, Northeastern Brazil - Caminha, Maria de Fátima Costa; Batista Filho, Malaquias; Serva, Vilneide Braga; Arruda, Ilma Kruze Grande de; Figueiroa, José Natal; Lira, Pedro Israel Cabral de (Revista de Saúde Pública, 2010)
OBJECTIVE: To analyze time trends in the duration of exclusive breastfeeding and associated protection factors. METHODS: Prevalances for total breastfeeding and exclusive breastfeeding in a population of four-month-old infants were analyzed. Data were obtained from population surveys carried out in 1991, 1997, and 2006, with 935, 2081, and 1568 infants respectively. The data were retrieved from interviews answered by parents or guardians. The prevalences were analyzed by Poisson regression in regard to: environmental, behavioral and socioeconomic conditions, maternal variables, and biological factors of infant. RESULTS: The median duration of total breastfeeding rose from 89 days (1991) to 106 days (1997), and finally to 183 days (2006). The median duration of exclusive breastfeeding remained around 30 days between 1997 and 2006. In the multivariate analysis, from the ten variables studied, only maternal schooling and age, address, and female gender of infant were maintained in the final explanatory model. CONCLUSIONS: Despite the significant increase in terms of total breastfeeding duration, the same did not occur with the duration of exclusive breastfeeding.